Dynamic Analysis of Support Bracket of the Oceanic Bridge Fabrication Machine (Movable Formwork) - Zongshuai Zhou; Linjian Shangguan (Journal of Marine Science and Engineering)
This study aims to evaluate the vibration and response performance of the core component support bracket in the DXZ32/900 oceanic bridge fabrication machine (movable formwork) to provide a foundation for its structural optimization. A finite element model of the support bracket is established, and three analyses are conducted: modal analysis to determine inherent frequencies and vibration modes, harmonic response analysis to evaluate steady-state behavior under sinusoidal loads, and transient dynamic analysis to assess displacement responses to dynamic loads. The frequency distribution indicates that the natural frequencies are densely packed without abrupt jumps, reflecting the complexity of the dynamic performance of the support bracket. Moreover, frequencies below the fourth order exhibit minimal deformation and limited impact on the overall dynamics. Sensitivity analysis is conducted to evaluate the impact of sectional parameter optimization on material efficiency and dynamic performance, ensuring robust design improvements. In summary, the findings reveal key vibration characteristics and response patterns, providing theoretical insights to guide the improvement of the support bracket and ensure the safety and efficiency of the bridge fabrication machine.